2015
DOI: 10.1016/j.cell.2015.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Ig Superfamily Ligand and Receptor Pairs Expressed in Synaptic Partners in Drosophila

Abstract: Summary Information processing relies on precise patterns of synapses between neurons. The cellular recognition mechanisms regulating this specificity are poorly understood. In the medulla of the Drosophila visual system, different neurons form synaptic connections in different layers. Here, we sought to identify candidate cell recognition molecules underlying this specificity. Using RNA sequencing (RNA-seq), we show that neurons with different synaptic specificities express unique combinations of mRNAs encodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
292
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(329 citation statements)
references
References 59 publications
22
292
2
Order By: Relevance
“…These results are consistent with the findings of a recent a cell-type specific RNA sequencing study (Tan et al, 2015), which showed that, at the onset of targeting, Fra is the only Net receptor expressed in R8 above 1–2 RPKM, the common threshold for noise in these types of studies.…”
Section: Resultssupporting
confidence: 92%
“…These results are consistent with the findings of a recent a cell-type specific RNA sequencing study (Tan et al, 2015), which showed that, at the onset of targeting, Fra is the only Net receptor expressed in R8 above 1–2 RPKM, the common threshold for noise in these types of studies.…”
Section: Resultssupporting
confidence: 92%
“…PN subtype identity is largely determined by a combinatorial code that utilizes a number of genes between the number of subtypes and the theoretical minimum for a maximally compact code, suggesting redundancy. The transcriptomes of closely related PN classes differed substantially during development (Figure 7F; Table S1), consistent with a recent report that closely related retinal cells have dozens of differentially expressed CSMs (Tan et al, 2015). A certain degree of redundancy can provide robustness to wiring precision (Hong and Luo, 2014), but creates challenges for dissecting genetic control of wiring specificity using single gene manipulation.…”
Section: Discussionsupporting
confidence: 89%
“…Brains containing cells labeled by mCD8GFP driven from specific GAL4 lines were manually dissected, single-cell suspensions were prepared following a method modified after Tan et al (2015), and cDNA were sequenced using a modified SMART-seq2 protocol (Picelli et al, 2014) (Figure 1B; Figure S1A; STAR Methods). We sequenced cells from Drosophila pupal brains that were labeled by the astrocyte driver alrm-GAL4 (Doherty et al, 2009) and olfactory projection neurons (PNs) labeled by the GH146-GAL4 driver, which is expressed in 40 of 50 PN classes (Stocker et al, 1997; Jefferis et al, 2001) (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual Dm8s exhibit variable, non-deterministic coverage patterns, raising questions about synaptic specificity [29,3234]. Recent findings on Ig superfamily cell adhesion molecules (21 Dprs and 9 DIPs) show that different Dm8 subtypes and their specific presynaptic R7 partners express interacting molecular pairs [35,36]. Dpr11 exhibits remarkably specific expression in R7 cells of the ‘yellow’ type (yR7), and it is unclear if an identical number of Dm8s express the presumptive matching interaction partner DIP-γ.…”
Section: Columns and Mosaics In Synaptic Specificationmentioning
confidence: 99%